THE EFFECTIVENESS OF VIDEO AND BANNER MEDIA ON IMPROVING KNOWLEDGE, ATTITUDE AND ACTION OF HIV EXAMINATION IN PREGNANT WOMEN - Ismiati Ismiati (Poltekkes Kemenkes Bengkulu, 2022)
Human Immunodeficiency Virus (HIV) is a virus that attacks the human immune system and causes Acquired Immuno-Deficiency Syndrome (AIDS) to death. Indonesia is one of the countries in Asia that is experiencing an HIV-AIDS epidemic with a prevalence that is increasing every year. Data from the Bengkulu Provincial Health Office in 2018 found that Kaur Regency ranks the lowest for pregnant women who carry out HIV tests, namely 0% because there is no HIV examination available for pregnant women, the second place is South Bengkulu Regency 9.27%, the third is Seluma District 16.35%, the fourth Bengkulu City was 22.07%, the five North Bengkulu Districts were 34.25%, the six Rejang Lebong Districts were 37.25% and the seven Muko-Muko Districts were 47.65%. The general objective of the study was to determine the differences in the use of health promotion media on the knowledge, attitudes and behavior of HIV testing in pregnant women in the work area of ??the Bintuhan Public Health Center, Kaur Regency, Bengkulu Province. This type of research uses a quasi-experimental method with a research population of 1284 women of childbearing age. Data retrieval using primary data which is divided into three groups, namely a video group of 25 people, the second Banner 25 people and the third Poster 25 people. The results showed that there was an increase in the skills of cadres in carrying out breast examinations before and after training from 25 to 75 and there was no effect of breast examination counseling on the skills of cadres. Suggestions are expected that the puskesmas can cooperate with the Health Office so that training can be carried out for Cadres on breast cancer.